2021
DOI: 10.3389/fpsyt.2021.566368
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum and Other Neurodevelopmental Disorders in Children of Immigrants: A Brief Review of Current Evidence and Implications for Clinical Practice

Abstract: Children of immigrants may have higher neurodevelopmental risks than those of non-immigrant populations. Yet, some evidence suggests that this group may receive late diagnosis, and therefore miss beneficial early interventions. Clinicians may misattribute symptoms of disorders to other social, behavioral or language problems. Likewise, there might be cultural differences in parents' likelihood of perceiving or reporting first developmental concerns to clinicians. Population-based standardized screening may pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 155 publications
0
26
0
Order By: Relevance
“…Stigma and discrimination are common elements in the community that culminate in shame and guilt. Therefore, the parents of children with ASD might feel embarrassed of their situation, prompting the withdrawal of the child from the public eye [ 6 ]. A lack of social support also means that parents might not have the right structure to deal with their children with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stigma and discrimination are common elements in the community that culminate in shame and guilt. Therefore, the parents of children with ASD might feel embarrassed of their situation, prompting the withdrawal of the child from the public eye [ 6 ]. A lack of social support also means that parents might not have the right structure to deal with their children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of social support also means that parents might not have the right structure to deal with their children with ASD. If the community is not well-structured to embrace such cases of disabilities, access to care might be a challenge [ 6 ]. Based on the nature of migrant communities, their beliefs might be different from those of the health service providers within the host countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although genetics play an important role with regard to the risk of ASD and symptoms of neurodevelopmental delay, evidence suggests that certain environmental exposures could also be involved [ 7 ]. Media screen exposure is a candidate, as children who early on in life spend a lot of time watching screens – particularly if their content is poor and/or if they are unsupervised—are less likely to play, be physically active, and engage in interactions with other children and adults, all of which could be related to worse neurodevelopmental outcomes [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has confirmed that children from immigrant backgrounds were at higher risk of having neurodevelopment disorders, including autism (Becerra et al, 2014;Schmengler et al, 2021). Research has been limited and inconsistent regarding the risk level for children of immigrants related to other disabilities (Schmengler et al, 2021).…”
Section: Misdiagnosis and Other Developmental Disorders For Latino Ch...mentioning
confidence: 99%